Sentinels in Salmon Aquaculture: Heart Rates Across Seasons and During Crowding Events - Warren-Myers, Fletcher; Hvas, Malthe; Vågseth, Tone; Dempster, Tim; Oppedal, Frode (Frontiers in Physiology, 2021)
Advances in tag technology now make it possible to monitor the behaviour of small groups of individual fish as bio-indicators of population wellbeing in commercial aquaculture settings. For example, tags may detect unusual patterns in fish heart rate, which could serve as an early indicator of whether fish health or welfare is becoming compromised. Here we investigated the use of commercially available heart rate bio-loggers implanted into 24 Atlantic salmon weighing 3.6 ± 0.8 kg (mean ± SD) to monitor fish over 5 months in a standard 12 m × 12 m square sea cage containing ~ 6000 conspecifics. Post tagging, fish established a diurnal heart rate rhythm within 24 hr which stabilized after 4 days. While registered tagged fish mortality over the trial period was 0%, only 75% of tagged fish were recaptured at harvest, resulting in an unexplained tag loss rate of 25%. After 5 months, tagged fish were approximately 20% lighter and 8% shorter, but of similar condition when compared to untagged fish. Distinct diurnal heart rate patterns were observed and changed with seasonal day length of natural illumination. Fish exhibited lower heart rates at night (Winter 39 ± 0.2 bpm, spring 37 ± 0.2 bpm, summer 43 ± 0.3 bpm, mean ± SE) than during the day (Winter 50 ± 0.3 bpm, spring 48 ± 0.2 bpm, summer 49 ± 0.2 bpm) with the difference between night and day heart rates near half during the summer (6 bpm) compared to winter and spring (both 11 bpm). When fish experienced moderate and severe crowding events in early summer, highest hourly heart rates reached 60 ± 2.5 bpm and 72 ± 2.4 bpm, respectively, on the day of crowding. Here, if the negative sub-lethal effects on fish that carry tags (e.g., growth rate) can be substantially reduced, the ability to monitor diurnal heart rate patterns across seasons and detect changes during crowding events, using heart rate bio-loggers could be a useful warning mechanism for detecting sudden changes in fish behaviour in sea cages.